Peran LPA Dalam Melindungi Hak Anak Yang Menjadi Pelaku Tindak Pidana (Lembaga Perlindungan Anak Jawa Timur) - Omarsyah, Mochammad; Hendrawan, Talby Maulana (Sanskara Hukum dan HAM, 2024)
Child Protection Agency (LPA) is a non-governmental organization that focuses on child protection, especially children from underprivileged families in Indonesia. Established in 1997, LPA is instrumental in safeguarding children's rights through child care and assistance. Child protection agencies work closely with partners at the local level to ensure that children's rights are fulfilled and to prevent them from being taken away by adults. Child protection is regulated in various laws, including the Child Protection Act and the Juvenile Justice System Act. LPA's role includes providing legal assistance to children in conflict with the law, ensuring they receive adequate representation, and advocating for child-friendly legal reforms. In addition, LPA also provides psychological and social support, and ensures that children who are perpetrators of criminal offenses, including homicide, receive appropriate protection and rehabilitation. LPA is also committed to the process of reintegrating children into society after serving their sentences, and tries to overcome various obstacles such as lack of community support and inconsistency of legal authorities. Diversion efforts as an alternative to resolving children's cases are also prioritized to avoid negative stigma and ensure the protection of children's rights.